DIAGNOSA KEADAAN GIZI ANAK MENGGUNAKAN METODE CASE BASED REASONING - Sutoyo, Muh. Nurtanzis (Fakultas Teknik, Universitas Tadulako, 2019)
Nutrition can occur in every phase of life, beginning in the womb until old age. This nutritional issue is also one of the main issues in human development. Implementation of Case Based Reasoning can help diagnose a child's nutritional status. Case-based reasoning (CBR) is a problem-solving method that uses the knowledge of past experience to solve new problems. From the results of research methods Case Based Reasoning can be used to diagnose the nutritional status of children. Where the application of Case-Based Reasoning (CBR) method for case studies of children's nutritional status diagnosis has achieved accuracy of more than 90%.